Development of a Game-Based e-Media "Snake Ladder Lumpia" to Enhance Vocab ulary Acquisition in Elementary Students - Mustikasari, Dyah Pramesti; Purwati, Panca Dewi (Jurnal Pendidikan Progresif, 2025)
Abstract: Development of a Game-Based e-Media "Snake Ladder Lumpia" to Enhance Vocab ulary Acquisition in Elementary Students. Objectives: Students' ability to interpret vocabulary is still low, which is the basis for this study. Students have been able to read but are still lacking in interpreting vocabulary. The use of learning media is still limited and there is no special media for learning Indonesian. Utilizing digital technology or making simple props relevant to the material, teachers can be more creative and use more diverse and innovative learning media. The purpose of this study aims to determine the feasibility and effectiveness of E-Media Snake Ladder Lumpia  in improving student learning outcomes in the material of interpreting vocabulary of grade IV elementary school students. Methods: This research uses the Research and Development (R&D) method with the Borg and Gall model. The product validity test was carried out with two validators, namely material expert validators and media expert validators. Data collection was carried out by interview, observation, test and non-test techniques. Data collected using a questionnaire. Analysis techniques used in this research are qualitative and quantitative. Findings: The results of this study indicate that the results of the feasibility test, the media obtained 95% with a very feasible predicate and the results of the feasibility test from the material expert 95% with a very feasible predicate. Conclucion: The results of the large-scale usage trial increased from the pretest and posttest with an average N-Gain of 0.63 and significance (2-tailed) of 0.00 < 0.05. The conclusion from the results of this study shows that the E-Media Ular Tangg Lumpia is declared feasible and effective in improving the competence of interpreting vocabulary of fourth grade students of SDN Bringin 02 Semarang.